Cloud Accounting pada Laporan Keuangan Perspektif Literatur - Filo Mena Cardoso (Journal of Academia Perspectives, 2023)
Managing financial statements aims to make it easier for users in this case the company to improve data, transactions and the presentation of financial reporting in real time. The purpose of this study is to know the basic concepts and how cloud accounting works, the functions and models of cloud accounting, the concepts and functions and components of financial position reports in cloud accounting with a work system of managing transactions to produce financial reports using internet media. The method is used by reviewing based on literature on the topic of cloud accounting and financial statements. As a result, the presentation and disclosure of information technology-based financial statements reduces the company's operational burden including data storage and servers. The use of internet media-based technology in managing financial transactions can produce and facilitate the presentation of financial reports anytime and anywhere. Then it's time for the accountant profession to update knowledge and skills in utilizing accounting information technology, especially in conducting accounting checks on clients using cloud accounting.